Template‐Free Scalable Fabrication of Linearly Periodic Microstructures by Controlling Ribbing Defects Phenomenon in Forward Roll Coating for Multifunctional Applications. Issue 27 (26th August 2022) - Islam, Md Didarul; Perera, Himendra; Black, Benjamin; Phillips, Matthew; Chen, Muh‐Jang; Hodges, Greyson; Jackman, Allyce; Liu, Yuxuan; Kim, Chang‐Jin; Zikry, Mohammed; Khan, Saad; Zhu, Yong; et al.
Abstract: Periodic micro/nanoscale structures from nature have inspired the scientific community to adopt surface design for various applications, including superhydrophobic drag reduction. One primary concern of practical applications of such periodic microstructures remains the scalability of conventional microfabrication technologies. This study demonstrates a simple template‐free scalable manufacturing technique to fabricate periodic microstructures by controlling the ribbing defects in the forward roll coating. Viscoelastic composite coating materials are designed for roll‐coating using carbon nanotubes (CNT) and polydimethylsiloxane (PDMS), which helps achieve a controllable ribbing with a periodicity of 114–700 µm. Depending on the process parameters, the patterned microstructures transition from the linear alignment to a random structure. The periodic microstructure enables hydrophobicity as the water contact angles of the samples ranged from 128° to 158°. When towed in a static water pool, a model boat coated with the microstructure film shows 7%–8% faster speed than the boat with a flat PDMS film. The CNT addition shows both mechanical and electrical properties improvement. In a mechanical scratch test, the cohesive failure of the CNT‐PDMS film occurs in ≈90% higher force than bare PDMS. Moreover, the nonconductive bare PDMS shows sheet resistance of 747.84–22.66 Ω □ −1 with 0.5 to 2.5 wt% CNT inclusion. Abstract : Nanocomposite coating pastes are formulated with tailored viscoelastic properties by loading multiwall carbon nanotubes in polydimethylsiloxane. The cylindrical inclusion transforms the fluid‐like polymer into yield‐stress materials. The composite under roll‐to‐roll shear exhibits controllable ribbing that demonstrates the first template‐free manufacturing of linearly periodic 3D microtrench structures. The micropatterned surface exhibits multifunctionality, including superhydrophobicity, hydrodynamic drag reduction, and electrical conductivity.